Chronic pain and cognitive dysfunction: clinical manifestations, underlying mechanisms, and emerging therapeutic strategies - Gong, Taowu; Yu, Wanqiu; Zhao, Pengcheng; Wu, Zhenyu; Zhu, Yuhang; Gong, Qihai; Zhu, Zhaoqiong (Frontiers in Neuroscience, 2025)
Chronic pain affects up to 60% of the population and not only impairs physical function but also leads to multidimensional neurocognitive deficits, including diminished attention, working memory impairment, and executive dysfunction. Clinical studies indicate that chronic pain induces gray matter atrophy in key brain regions, such as the prefrontal cortex and hippocampus, along with disrupted functional connectivity and other pathological alterations. Despite extensive research, the precise pathogenic mechanisms remain largely unclear, making this a central focus of current investigations. In this review, we examine the morphological and functional changes in these critical brain regions from an anatomical perspective. By integrating cellular and molecular insights, we elucidate the multi-level mechanisms underlying chronic pain-induced cognitive impairment. Furthermore, we summarize current therapeutic strategies, including pharmacological treatments, neuromodulation, and behavioral interventions, and discuss promising directions for future research. By synthesizing recent advances, this review aims to enhance understanding of the clinical manifestations and pathophysiology of chronic pain, thereby informing the development of more effective diagnostic and therapeutic approaches.